Deteksi Letak Kebocoran Pipa Berdasarkan Analisis Debit Air Menggunakan Teknologi Sensor Flowmeter Berbasis TCP/IP - Duwi Hariyanto; Gurum Ahmad Pauzi; Amir Supriyanto (Jurnal Teori dan Aplikasi Fisika, 2017)
Pipeline leaks can cause major financial losses for the users of pipeline system. Perusahaan Daerah Air Minum (PDAM) generally uses manual methods to detect leak location, such as by looking puddle above the pipeline. The research proposed to produce a method that can detect pipeline leak location quickly and accurately. The method use water flow sensors that are placed before and after the leak. The water flow sensors are used to record data of the difference between incoming and outgoing water flow (?Q). The data are transmitted to a computer using a network based on TCP/IP. The results showed that the smaller value of the difference between incoming and outgoing water flow (?Q), the farther distance leak location (X). If diameter hole (D) had decreased by 43%, the value of the difference between incoming and outgoing water flow (?Q) would have decreased by 21%. Based on these results, the method for detecting pipeline leak location with technology water flow sensors can distinguish pipeline leak location quickly and accurately.